PENGEMBANGAN LEMBAR KERJA SISWA MATEMATIKA BERBASIS CTL UNTUK SISWA KELAS VII SMP MATERI ARITMATIKA SOSIAL - Dianita, Fitria (Universitas Pasir Pengaraian, 2016)
This study aims to produce a device in the form of mathematics learning Student Worksheet (LKS) math-based Contextual Teaching and Learning on the subject of social arithmetic for Junior High School class VII. This research was the development (Research and Development) with a 3-D model of development which includes the step of defining, the designÂ and developing. The subjects were students of class VII Junior High School 5 Rambah Hilir, 2015/2016. The instrument used in this study was validation questionnaire sheet and questionnaire sheet practicalities. Based on the test validity based Student Worksheet Contextual Teaching and Learning that had been rated by four raters with some revisions and corrections, then it was obtained that average score of validation results-based Student Worksheet Contextual Teaching and Learning is at 3.13 categorized to valid category. While the practicalities obtained based on testing and assessment by an expert using a questionnaire practicalities Expert with an average of 79% with the practicality of a practical category, teacher with an average of 81% with the practicality of a practical category and class VII Junior High School 5 Rambah Hilir with an average 84% with a practical category. Finally, it could be concluded that based Student Worksheet Contextual Teaching and Learning was valid and practiced.